Targeting α- and β-Adrenergic Receptors Differentially Shifts Th1, Th2, and Inflammatory Cytokine Profiles in Immune Organs to Attenuate Adjuvant Arthritis - Lubahn, Cheri L.; Lorton, Dianne; Schaller, Jill A.; Sweeney, Sarah J.; Bellinger, Denise L. (Frontiers in Immunology, 2014)
The sympathetic nervous system (SNS) regulates host defense responses and restores homeostasis. SNS-immune regulation is altered in rheumatoid arthritis (RA) and rodent models of RA, characterized by nerve remodeling in immune organs and defective adrenergic receptor (AR) signaling to immune cell targets that typically promotes or suppresses inflammation via α- and β2-AR activation, respectively, and indirectly drives humoral immunity by blocking Th1 cytokine secretion. Here, we investigate how β2-AR stimulation and/or α-AR blockade at disease onset affects disease pathology and cytokine profiles in relevant immune organs from male Lewis rats with adjuvant-induced arthritis (AA). Rats challenged to induce AA were treated with terbutaline (TERB), a β2-AR agonist (600 μg/kg/day) and/or phentolamine (PHEN), an α-AR antagonist (5.0 mg/kg/day) or vehicle from disease onset through severe disease. We report that in spleen, mesenteric (MLN) and draining lymph node (DLN) cells, TERB reduces proliferation, an effect independent of IL-2. TERB also fails to shift Th cytokines from a Th1 to Th2 profile in spleen and MLN (no effect on IFN-γ) and DLN (greater IFN-γ) cells. In splenocytes, TERB, PHEN and co-treatment (PT) promotes an anti-inflammatory profile (greater IL-10) and lowers TNF-α (PT only). In DLN cells, drug treatments do not affect inflammatory profiles, except PT, which raised IL-10. In MLN cells, TERB or PHEN lowers MLN cell secretion of TNF-α or IL-10, respectively. Collectively, our findings indicate disrupted β2-AR, but not α-AR signaling in AA. Aberrant β2-AR signaling consequently derails the sympathetic regulation of lymphocyte expansion, Th cell differentiation, and inflammation in the spleen, DLNs and MLNs that is required for immune system homeostasis. Importantly, this study provides potential mechanisms through which reestablished balance between α- and β2-AR function in the immune system ameliorates inflammation and joint destruction in AA.